A Study on the Forgiveness Concept of Aceh Conflict Victims - Hafnidar Hafnidar; Nursan Junita; Ratna Ratna (Proceedings of AICS - Social Sciences, 2017)
Acehnese people experience traumatic experiences due to conflict and prolonged war in Aceh. This research was conducted by using phenomenology as a qualitative method. The aims of research are to find the forgiveness basic concept of Aceh people. The total of research participants were 10 respondents which chosen from Aceh conflict victims by using purposive sampling technique, that is based on the following predetermined criteria: (1) is one of the following elements: Islamic leaders, scholars, casualty in remote areas and urban area, social activists, political organization activist, government official, housewife, as well as representatives of each profession in society, (2) Represents direct victims of Aceh conflict, (3) A native Acehnese and have lived in Aceh since the Aceh conflict (1976) until now. The data collection methods utilized in-depth interviews, observation, and analysis of documentation. This study applied the important principles in a phenomenology research: epoch, phenomenological reduction, imaginative variation, and synthesis of meanings and essences. The concept of forgiveness varies depending on the socio-cultural norms of each individual. The results reveal that for the Acehnese who are rooted in the conceptualized culture of Islam, the concept of forgiveness is closely related to the concept of spirituality, post traumatic growth (PTG), and coping strategic and positive self-concept.